Efforts to Improve PAI Learning Through The Critical Thinking Model - Surawan Surawan; Arzakiah Arzakiah (Journal of Contemporary Islamic Education, 2022)
This article is focused on improving PAI learning by using the Critical Thinking model. This study uses a qualitative approach with a descriptive methodology, observation and analysis. In the world of education, of course, it cannot be separated from the role of an educator who builds and creates a better young generation as the successor of knowledge. To achieve these learning objectives, teachers and students must work well together so that the material and knowledge conveyed can be absorbed properly as well. Basically this research aims to focus on cognitive abilities, critical thinking, active, independent and creative. Efforts that can be implemented are improving the quality of PAI learning through critical thinking models.